Gambaran Kebutuhan Orangtua Dengan Bayi Yang Sakit Kritis di RSUD Prof.dr. Margono Soekarjo Purwokerto - SIWI, ADIRATNA SEKAR (Viva Medika, 2019)
Patient’s parent is an essential part of holistically care treatment, especially when the patients are still too young to responsible for their own. Nurse have to understand regarding parents need to deliver high quality care for patients and their family. Parents’ needs during accompanying their children could be very specific and unique. The knowledge regarding this issue is crucial to increase the quality of care and prevent parents’ psychological problem. This is a descriptive study with cross sectional approach. Total sample in this study are respondent who are chosen by using consecutive sampling. The NICU Family Needs Inventory (NFNI) was used in this study. This study shows that the parents’ needs during accompanying their children in critical care setting are need for closeness with their children, Certainty regarding patient condition, comfort, information, and the needs of support.